Zlepšení kognitivních funkcí a zaměstnanosti u pacientů s relabující formou roztroušené sklerózy léčených okrelizumabem - Peterka, Marek (Neurologie pro praxi, 2023)
Cognitive impairment has a significant impact on the quality of life of MS patients. It leads to impairment in social activities, physical independence, ability to manage daily activities, ability to take regular medication and employment. The aim of modern treatment should not only be to achieve stabilisation of the disease, but also to improve cognitive function and therefore employment. This article presents recent information on the positive effect of ocrelizumab treatment on these parameters.
Keywords: studie CASTING; Humans; neuropsychologické testy; multicentrické studie jako téma; kognice; lidé; humanizované monoklonální protilátky; intravenózní podání; Employment; Antibodies, Monoclonal, Humanized; Multiple Sclerosis, Relapsing-Remitting; Neuropsychological Tests; relabující-remitující roztroušená skleróza; zaměstnanost; Administration, Intravenous; prospektivní studie; Cognition; okrelizumab; Multicenter Studies as Topic; Symbol Digit Modalities Test; Prospective Studies